Analisis Digital Marketing Dan Reference Group Terhadap Peningkatan Jumlah Pelanggan Jasa Fotografi (Studi Kasus Pada Noic Studio Kediri) - Mukhamad Rinda Rifa'i; Eka Askafi; Sumarji Sumarji (REVITALISASI : Jurnal Ilmu Manajemen, 2022)
Marketing includes all activities of the company in adapting to its environment creatively and profitably. Because success in competition will be achieved if the company can create and retain its customers. This has triggered the shift of Noic Studio's marketing strategy from offline marketing to a Digital Marketing strategy, so the promotions and information carried by Noic Studio will be more optimal, effective and efficient, as well as strengthen the sense of trust from customers to become the Reference Group for marketing their photography services. Based on the results of research interviews, it was obtained information that Noic Studio had tried to carry out both strategies optimally but there were several things that had to be optimized, especially in the implementation of the Reference Group strategy. Which was supported by the results of SPSS research partially obtained Digital Marketing (X1) has a Tvalue of 5.720 with sig=0.000 which means that Digital Marketing (X1) has a positive effect on the increase Noic’s customers, While the Reference Group (X2) has a Tvalue of 0.723 with sig=0.472 which means that the Reference Group (X2) does not have a significant effect on the increase. in the number of customer in NOIC studio. Keywords: Marketing, Customer, Noic Studio, Digital Marketing, Reference Group, Interview, SPSS